Effects of cinnamic acid on the root growth of cucumber (cucumis sativus l.) and figleaf ground (cucurbita ficifolia bouché) seedlings - Qiao, Yongxu; Zhang, Yongping; Wang, Ziying; Gao, Lihong (Bangladesh Journal of Botany, 2024)
Effect of cinnamic acid (CA) on growth and endogenous hormone content in the roots of cucumber and figleaf gourd seedlings were studied and explained the reason why figleaf gourd was better in resisting CA stress than cucumber using their seedlings as experimental materials. The effect of CA at different concentrations (0, 0.05, 0.10, 0.15, 0.20 and 0.25 mmol/l) was analysed on primary root elongation, total root elongation, average diameter of total roots, total root volume, and total root tips as well as the effects of 0 and 0.25 mmol/l CA on root growth, root density, root hair growth rate, indole acetic acid (IAA) content and ethylene (ET) production rate. The results showed that CA stress decreased the primary root elongation, total root elongation, total root tips, Grade III root and root hair growth rates of both plants. The inhibiting effect of CA was stronger on cucumber than figleaf gourd. Besides, CA stress increased their average diameters of total roots and root hair densities. The increase in the average diameter of total roots of cucumber was larger than that of figleaf gourd while its increase in root hair density was far lower. Apart from that, 0.25 mmol/l CA stress increased the IAA contents and ET production rates in both kinds of roots. The increase in IAA content in cucumber root was 16% higher than in figleaf gourd. However, the increase in the ET production rate of cucumber root was 51% lower than figleaf gourd root. In conclusion, higher concentration IAA could inhibit root growth. Under CA stress, the increase in the IAA content in figleaf gourd root was lower than that in cucumber root, indicating that CA exerted a weaker inhibiting influence on figleaf gourd. Besides, higher ET production rate contributed to the increase in root hair density. Under CA stress, figleaf gourd root had a higher ET production rate than cucumber root, thus having more root hairs. Bangladesh J. Bot. 53(3): 703-710, 2024 (September) Special